KEEFEKTIFAN BIMBINGAN KELOMPOK DENGAN MENGGUNAKAN PERMAINAN UNTUK MENINGKATKAN MOTIVASI BERAFILIASI PADA MAHASISWA SEMESTER IV PROGRAM STUDI BIMBINGAN DAN KONSELING FKIP UNISRI TAHUN 2016/2017 - Eko Adi Putro (Universitas Slamet Riyadi, 2018)
Affiliate motive is a necessity that every individual needs. individuals need a needwhereby the need is one of them is the need to relate to others or the need to make friendshipswith others. Both women and men all need friends who can understand and understand it. Butnot all individuals can increase the need, because that need can only be increased by makingfriendship with others in which there is a sense of trust and empathy for each other. With theseelements the individual can feel that making friendships will feel beautiful when a sense oftrust and empathy become a support in making friendships. The purpose of this research is toknow the description of student affiliation motivation before and after being given groupguidance service and to know the difference of affiliated motivation before and after mengiitgroup guidance service. Motives are encouragement that causes individuals to be particular,whereas affiliated motivation is the motivation for forming and maintaining friendships withothers in which there is an element of trust, affection and empathy shown in a friendly manner.Group guidance is one counseling guidance service provided Counselors to some people ingroup situations (7-15 people) who discuss the actual general problem by utilizing groupdynamics. The type of research used is Quasi Eksperimen with research design using onegroup per-test and post-test design. This research uses purposive sampling technique onstudents who have low affiliation motivation. The method of data collection in this study is thescale of affiliated motivation. Test validity using Product Moment correlation formula rxy =0.422> rtabel = 0.325 and the reliability of the instrument using the formula Alpha r11 =0.928> rtabel = 0.325 it is concluded that the instances are reliable. Data analysis techniqueusing Wilcoxon test formula Zhitung = -3.298> Ztable = 0.21, it shows that student affiliationmotivation can be improved through group guidance service. From this research it can beconcluded that the image of motivation affiliated before being given group guidance servicesobtained 49.70% score with low category and after being given group guidance servicesobtained a score of 75.05% with high category. From these calculations means an increase inthe motivation of students affiliated IV Guidance and Counseling Study Program FKIP UnisriYear 2016/2017 between before and after the group guidance services provided.Keywords: Affiliated Motivation, Group Guidance.